Improving public equity markets? No pain, no Gain - Katya Kartashova (Bank of Canada, 2014)
This paper quantifies the effects of improving public equity markets on macroeconomic aggregates and welfare. I use an open-economy extension of Angeletos (2007), where entrepreneurs face idiosyncratic productivity risk in privately held firms. They can diversify by investing in publicly traded firms, but their operation is costly. These costs can vary across different economies. To quantify the effect of the differences and impose discipline, I parameterize the model using Ecuadorian and Chilean firm-level and aggregate data. Lower equity costs result in improvement of economic aggregates, but have differential welfare effects. Entrepreneurs suffer a loss, while workers gain.
Keywords: E44; G11; O11; O16; 330; Financial institutions; Financial markets; Development economics